Diabetes Mellitus Health Counseling in Jetis Village, Bondowoso : Penyuluhan Kesehatan Diabetes Mellitus di Desa Jetis, Bondowoso - Leni Agustin; Siti Riskika; Yuana Dwi Agustin (KHD Production, 2023)
An increase in the prevalence of diabetes mellitus (DM) sufferers has occurred throughout the world, where Indonesia ranks 4th for the number of DM sufferers worldwide. This is certainly a phenomenon that needs serious attention from the government and society. Diabetes mellitus is a chronic disease characterized by uncontrolled blood sugar levels that can cause permanent damage to organs such as the eyes, heart, kidneys, and blood vessels. Diabetes mellitus is possible for everyone to suffer from, both those with a hereditary history of suffering from DM and those who do not have a hereditary history. Activities carried out in preparation, implementation, and evaluation. The activity method used is a lecture equipped with leaflet media where a discussion then follows the activity. The activity results showed that the implementation of counseling went smoothly, with an explanation of the material regarding definitions, patient criteria, risk factors, ways to prevent management, and the introduction of blood sugar measuring devices. The very high enthusiasm of the participants in asking questions was obtained by 90% of the participants asking questions, with each questioner asking one to four questions. Participants proposed to carry out the follow-up of diabetes mellitus counseling in the form of blood sugar checks which would be carried out at the next study meeting. The conclusion is that education in the form of counseling has formed positive perceptions related to awareness of the importance of preventing and controlling diabetes mellitus.